Hydrothermally stable carbon-based catalyst as well as preparation method and application thereof
By reacting lignin with an alkaline solution and a metal salt and mixing it with a solvent gel reagent, a carbon-based catalyst with a multi-layer carbon sheet structure was prepared, which solved the problem of inactivation of the existing carbon-based catalyst under hydrothermal conditions, and achieved efficient and stable catalytic performance and recycling performance.
Patent Information
- Application Number
- CN202510128907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-05-09
AI Technical Summary
Existing carbon-based catalysts are prone to inactivate or passivation under hydrothermal conditions, resulting in poor recycling performance and stability, affecting industrial applications.
By reacting lignin with an alkaline solution and a metal salt, a lignin-metal composite is formed and mixed with solvent gel reagent. After stirring, centrifugation, drying and calcining, a carbon-based catalyst with a multi-layer carbon sheet structure is prepared, so that the metal active sites are encased in a carbon cage, and hydrothermal stability is improved.
It significantly improves the hydrothermal stability and catalytic performance of carbon-based catalysts, extends its service life, reduces the load of impurities, and improves the stability and efficiency of recycling.
Smart Images

Figure CN119951492A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass catalysis, and specifically relates to a hydrothermally stable carbon-based catalyst and a preparation method and application thereof. Background Art
[0002] Converting renewable biomass resources into high-quality biomass-based platform chemicals to replace fossil resources is of great significance for achieving carbon peak and carbon neutrality. Furfural is an important furan compound that can be used to prepare 2-methylfuran, 2,5-dimethylfuran, long-chain alkanes and pharmaceutical intermediates. Converting biomass and its derivatives into furfural through dehydration reaction is one of the important ways to efficiently utilize biomass.
[0003] At present, inorganic liquid acids such as sulfuric acid, hydrochloric acid, phosphoric acid, etc. are usually used as catalysts for the dehydration of biomass to produce furfural. There are problems such as difficult product separation, severe equipment corrosion, and environmental pollution. Carbon-based materials as catalysts not only have the function of liquid acids to provide protons and hydrogen, but also have the advantages of easy separation, recyclability, and regeneration. They are considered to have great potential to replace liquid acids and are green and sustainable catalytic materials. The efficient catalytic production of furfural from xylose by carbon-based catalysts can obtain a better yield of furfural.
[0004] The invention patent application with publication number CN117101719A discloses a lignin-based sulfonated carbon catalyst and its preparation method and application. This invention patent application uses lignin sulfonate, a by-product of the sulfite papermaking process, as a raw material. After carbonization and ion exchange, the sulfonic acid functional groups in the lignin sulfonate structure are fully retained to prepare a highly acidic high specific surface area sulfonated carbon catalyst, and converts cellulose into levulinic acid products in a one-step reaction in an aqueous solvent, avoiding the use of traditional highly corrosive substances such as sulfuric acid and hydrochloric acid and homogeneous catalysts such as ionic liquids, and the target product can be obtained in a one-step reaction. Compared with the use of strong oxidizing liquid acids and acidic ionic liquids, the process is green and environmentally friendly, and the yield and conversion rate are excellent. However, the carbon-based catalyst is easily deactivated or passivated under hydrothermal conditions, affecting its recycling performance and stability.
[0005] The invention patent application with the publication number CN114875443A discloses a lignin-based bimetallic catalyst and its preparation method and application. A preparation method for a lignin-based bimetallic electrocatalyst is provided, which is obtained by coordinating lignin with a transition metal to form a metal-carboxylated lignin complex after modification and then carbonizing and reducing it at high temperature. The method comprises the following steps: S1. Mixing the carboxylated lignin with the metal in steps and adjusting the pH and stirring the hydrothermal to obtain a metal oxide-carboxylated lignin complex; S2. Carbonizing the metal oxide-carboxylated lignin complex at high temperature to obtain a carboxylated lignin-based bimetallic catalyst. The lignin-based bimetallic catalyst obtained by the preparation method of the invention patent exhibits excellent catalytic activity for hydrogen evolution by electrolysis of water. However, the active sites of the catalyst disclosed in the invention patent are easily covered by impurities during the catalytic process, which affects the catalytic activity and stability.
[0006] The carbon-based catalysts disclosed in the prior art are easily deactivated or passivated under hydrothermal conditions, and their recycling performance and stability are poor, which is very unfavorable for the industrial application of carbon-based catalytic materials. On the one hand, in order to improve the catalytic performance of carbon-based catalysts, they are often surface activated, and the activators usually include sulfuric acid, perchloric acid and other reagents that have serious impacts on the environment, and the acid sites are very easy to fall off during the hydrothermal reaction;
[0007] On the other hand, as the number of uses increases, the active sites on the surface of carbon-based catalytic materials are easily covered or detached, resulting in a decrease in their catalytic activity. Therefore, the poor stability and short service life of carbon-based catalysts have become one of the main obstacles to industrial promotion. Summary of the invention
[0008] The invention provides a method for preparing a hydrothermally stable carbon-based catalyst. The carbon-based catalyst prepared by the preparation method has high catalytic performance and hydrothermal stability.
[0009] The present invention provides a method for preparing a hydrothermally stable carbon-based catalyst, comprising:
[0010] (1) adding lignin to an alkaline solution, then adding a metal salt, and centrifuging to obtain a lignin-metal complex;
[0011] (2) Mixing the lignin-metal complex with a solvent gel reagent to obtain a mixture, stirring the mixture, centrifuging and separating to obtain a precipitate, and drying and calcining the precipitate to obtain a carbon-based catalyst.
[0012] The present invention dissolves lignin by an alkaline solution, removes impurities and exposes more functional groups in the lignin, and then chelates the exposed functional groups with metal ions to form active sites, thereby improving the catalytic performance.
[0013] The present invention makes the lignin-metal complex evenly distributed in the solvent gel reagent by mixing and stirring in step (2), thereby reducing agglomeration. The solvent gel around the metal active site is carbonized by calcination to form a multi-layer carbon sheet, so that the metal active site is located in a carbon cage composed of the carbon sheets. In the hydrothermal reaction, the carbon cage protects the metal active site, and impurities formed during multiple reactions are difficult to be loaded onto the metal active site, thereby improving the hydrothermal stability. At the same time, since the metal active site is located in the carbon cage, it is difficult to detach, thereby improving the catalytic stability.
[0014] Preferably, in the mixture, the content of the solvent gel agent is 10wt%-80wt%.
[0015] The present invention controls the content of the solvent gel reagent so that the lignin-metal complex containing the metal active sites is evenly distributed and agglomeration is reduced. At the same time, it can also avoid the situation that the solvent gel reagent wrapping the lignin-metal complex is too thick, the number of carbon sheets around the metal active sites is too large after carbon burning, the pore size of the carbon sheets is too small, or even completely sealed, so that the metal active sites cannot participate in the catalytic reaction, and the catalytic performance and hydrothermal stability are affected.
[0016] Further preferably, the content of the solvent gel agent is 30wt%-50wt%. An appropriate amount of the solvent gel agent can fully disperse the lignin-metal complex through gelation during the mixing and stirring process with the lignin-metal complex, and the solvent gel agent can effectively protect the agglomeration of metal active sites by forming a carbon layer as a carbon source during calcination.
[0017] The present invention further controls the content of the solvent gel reagent, which is more conducive to the dispersion of the composite during the stirring and dispersing process and the appropriate pore size formed during the carbonization process, effectively forming stable metal active sites; and further controls the viscosity of the solvent gel reagent, which is also conducive to stirring and thus conducive to the effective dispersion of the lignin-metal composite.
[0018] Preferably, the solvent gel agent is one or more of polyvinyl alcohol, chitosan, carboxymethyl cellulose, starch, agar, and gelatin.
[0019] Further preferably, the solvent gel agent is polyvinyl alcohol. Since polyvinyl alcohol has better temperature sensitivity, the lignin-metal complex can be better dispersed in the polyvinyl alcohol, thereby further reducing agglomeration. At the same time, polyvinyl alcohol contains a large number of hydroxyl groups, and a large number of hydroxyl groups remaining after calcination can participate in the reaction.
[0020] Preferably, the carbonization temperature is 400°C-800°C, and the holding time is 30-180 minutes. The present invention controls the calcination temperature and holding time to carbonize the solvent gel reagent while avoiding graphitization.
[0021] Preferably, the calcination holding time is 60-120 minutes. The present invention further controls the calcination holding time to minimize pore damage and energy waste, while ensuring that carbonization is complete enough and metal active sites are sufficiently oxidized to avoid shedding.
[0022] Further preferably, the heating rate of the carbon calcination is 5°C / min-20°C / min.
[0023] Preferably, the alkaline solution is one or more of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, and a lithium hydroxide solution.
[0024] Preferably, the metal salt is one or more of tin chloride, ferric chloride, magnesium chloride, cobalt chloride, aluminum chloride, magnesium nitrate, aluminum nitrate and ferric nitrate.
[0025] Preferably, the mass ratio of the metal salt to lignin is 0.5wt%-5wt%.
[0026] Preferably, the drying temperature in step (2) is 40° C.-100° C., and the drying time is 12-48 hours.
[0027] Preferably, after obtaining the carbon-based catalyst, it is cooled to room temperature, then washed with deionized water and dried.
[0028] On the one hand, the present invention also provides a hydrothermally stable carbon-based catalyst, which is prepared by the preparation method of the hydrothermally stable carbon-based catalyst.
[0029] On the other hand, the present invention also provides the use of the hydrothermally stable carbon-based catalyst in the preparation of furfural by dehydration of biomass, comprising:
[0030] Xylose is used as a reaction substrate, and the reaction system is a reaction solvent of dichloromethane and water. Xylose and the hydrothermally stable carbon-based catalyst are added to a hydrothermal reactor, and then the reaction solvent is added. The reaction is carried out at 140° C. to 210° C. for 60 to 150 minutes, and the reaction is cooled and filtered. The filter residue is the carbon-based catalyst, which is washed and dried for standby use. The furfural in the filtered liquid is quantitatively analyzed by high performance liquid chromatography.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention uses a solvent gel reagent to evenly disperse the lignin-metal composite containing metal active sites to avoid agglomeration that affects the catalytic performance, and then converts the solvent gel reagent into carbon sheets by carbon calcination, so that the metal active sites are wrapped in a carbon cage composed of the carbon sheets. During the catalytic process, impurities decomposed from the substrate are mainly loaded on the carbon cage, avoiding excessive impurities on the metal active sites, thereby improving stability. At the same time, since the metal active sites are located in the carbon cage and are not easy to fall off, the catalytic performance is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the infrared spectrum of the carbon-based catalyst prepared in Example 6;
[0034] Figure 2 This is the pyridine infrared spectrum of the carbon-based catalyst prepared in Example 6;
[0035] Figure 3 is a morphology picture of the carbon-based catalyst prepared in Example 6;
[0036] Figure 4 is the infrared spectrum of the carbon-based catalyst prepared in Example 11;
[0037] Figure 5 is the pyridine infrared spectrum of the carbon-based catalyst prepared in Example 11;
[0038] Figure 6 is a morphology picture of the carbon-based catalyst prepared in Example 11;
[0039] Figure 7 These are ammonia adsorption spectra of the carbon-based catalyst prepared in Example 6 after being used once and 50 times;
[0040] Figure 8 This is a morphology diagram of the carbon-based catalyst prepared in Comparative Example 3. DETAILED DESCRIPTION
[0041] The following is a detailed description of a hydrothermally stable carbon-based catalyst, a preparation method and an application thereof of the present invention in conjunction with the accompanying drawings.
[0042] The metal salts and solvent gel reagents provided in Examples 1-10 of the present invention are shown in Table 1
[0043] Examples 1-10
[0044] This embodiment provides a method for preparing a hydrothermally stable carbon-based catalyst, comprising:
[0045] Accurately weigh 5.0 g of lignin and transfer it to 1000 mL of 3 g / L sodium hydroxide solution. After continuous stirring for 30 min, add 0.5 g of metal salt and continue stirring. After precipitation occurs, centrifuge the solid and liquid to obtain the solid, which is the lignin-metal complex.
[0046] Accurately weigh 1.0g of lignin-metal complex and add 1.0g of solvent gel reagent. Stir thoroughly at room temperature for 60min, then centrifuge and dry the precipitate in a 60°C oven for 24h. After drying, transfer it to a tubular furnace and carbonize it at 500°C for 30min at a heating rate of 10°C / min. After cooling to room temperature, wash it with a large amount of deionized water and dry it to obtain a lignin-derived hydrothermally stable carbon-based catalyst.
[0047] like Figure 1 As shown, the hydrothermally stable carbon-based catalyst prepared in Example 6 has abundant oxygen-containing functional groups, such as hydroxyl groups, carboxyl groups, etc.
[0048] like Figure 2 As shown, the hydrothermally stable carbon-based catalyst prepared in Example 6 has both Lewis acid (L) and Bronsted acid (B) acid sites.
[0049] like Figure 3 As shown, the morphology of Example 6, it can be seen from the figure that the obtained carbon catalyst has a porous structure and the formed structure is like a cage, locking the oxide of the formed metal catalytic site.
[0050] Table 1 shows the metal salts and solvent gel reagents used in different examples
[0051]
[0052]
[0053] Embodiment 11
[0054] The difference from Example 6 is that the added amount of polyvinyl alcohol is 30 wt %.
[0055] like Figure 4 As shown, the hydrothermally stable carbon-based catalyst prepared in this example has abundant oxygen-containing functional groups, such as hydroxyl groups, carboxyl groups, etc.
[0056] like Figure 5 As shown, the hydrothermally stable carbon-based catalyst prepared in this example has both Lewis acid (L) and Bronsted acid (B) acid sites.
[0057] like Figure 6 As shown, the obtained hydrothermally stable carbon-based catalyst has a porous structure similar to a cage, in which there are active sites of metal oxides.
[0058] Comparative Example 1
[0059] Preparation of a hydrothermally stable carbon-based catalyst: Accurately weigh 5.0 g of lignin, transfer it to 3 g / L 1000 mL of sodium hydroxide solution, continue stirring for 30 minutes, then add 1.0 g of polyvinyl alcohol, fully stir at room temperature for 60 minutes, then centrifuge and dry the precipitate in a 60°C oven for 24 hours, after drying, transfer it to a tubular furnace and carbonize it at 500°C for 30 minutes at a heating rate of 10°C / min, cool to room temperature, wash with a large amount of deionized water, and dry to obtain a lignin-derived hydrothermally stable carbon-based catalyst.
[0060] Comparative Example 2
[0061] Preparation of a hydrothermally stable carbon-based catalyst: Accurately weigh 5.0 g of lignin, transfer it to 1000 mL of 3 g / L sodium hydroxide solution, continue stirring for 30 minutes, then add 0.5 g of tin tetrachloride, continue stirring, and centrifuge the solid and liquid after precipitation. The solid obtained is the lignin-tin complex.
[0062] Accurately weigh 1.0 g of lignin-tin complex, stir thoroughly at room temperature for 60 min, then centrifuge and dry the precipitate in a 60 °C oven for 24 h. After drying, transfer it to a tubular furnace and carbonize it at 500 °C for 30 min at a heating rate of 10 °C / min. After cooling to room temperature, wash it with a large amount of deionized water and dry it to obtain a lignin-derived hydrothermally stable carbon-based catalyst.
[0063] Comparative Example 3
[0064] Compared with Example 6, the difference is that the amount of polyvinyl alcohol added is 90wt%. Figure 8 As shown, it can be seen that the pore structures of some hydrothermally stable porous carbon materials are partially blocked.
[0065] Application Examples 1-11, Comparative Examples 4-6
[0066] In the present application examples 1-11 and comparative examples 4-6, the hydrothermally stable carbon-based catalysts prepared in examples 1-11 and comparative examples 1-3 are used to convert xylose into furfural. The specific preparation steps are as follows:
[0067] 1.0 g of xylose, 5.0 g of dimethyl sulfoxide, 5.0 g of ultrapure water, and 0.1 g of the hydrothermally stable carbon-based catalyst prepared in Example 1-10 were added, and the reaction temperature was 170° C. and the reaction time was 120 min. After the reaction was completed, the solid was separated by centrifugation, the separated solid was the catalyst, and the liquid was furfural. The hydrothermally stable carbon-based catalyst was dried and reused.
[0068] The furfural yields of the carbon-based catalysts prepared using different embodiments are shown in Table 2. It can be seen from Table 2 that the carbon-based catalysts prepared using Embodiments 1 to 11 can efficiently convert xylose into furfural, and the furfural yield is relatively high, especially when polyvinyl alcohol is used as the solvent gel reagent. Since polyvinyl alcohol has high temperature sensitivity, tin chloride can be evenly dispersed therein, and a large number of carboxyl groups participate in the catalytic reaction after carbon calcination, so the furfural yield is the highest. In Comparative Example 3, due to the narrow or blocked pore channel, the metal active sites are seriously affected to participate in the reaction, and therefore, the furfural yield is relatively low.
[0069] like Figure 7 As shown, the ammonia adsorption spectra of the carbon-based catalyst prepared in Example 6 after being used once and 50 times indicate that the catalyst has not undergone significant changes during the hydrothermal reaction and its active sites remain unchanged, which is why the furfural yield is still relatively high after multiple cycles.
[0070] In Application Example 6, the carbon-based catalyst prepared in Example 6 was recycled for multiple times, and in Comparative Examples 4-5, the corresponding carbon-based catalysts were recycled for multiple times. The specific number of cycles, xylose conversion rate and furfural yield are shown in Table 3. It can be seen that the furfural yield of the carbon-based catalyst prepared in Example 6 is still relatively high when the number of cycles reaches 50, while the furfural yields of Comparative Examples 1 and 2 are significantly reduced when the cycles are 20 and 30, respectively.
[0071] Table 2 shows the yield of xylose converted into furfural using carbon-based catalysts prepared in different embodiments
[0072] Application Examples Carbon-based catalyst used Furfural yield / % Application Example 1 Carbon-based catalyst prepared in Experimental Example 1 82.5 Application Example 2 Carbon-based catalyst prepared in Experimental Example 2 81.6 Application Example 3 Carbon-based catalyst prepared in Experimental Example 3 72.8 Application Example 4 Carbon-based catalyst prepared in Experimental Example 4 78.7 Application Example 5 Carbon-based catalyst prepared in Experimental Example 5 71.2 Application Example 6 Carbon-based catalyst prepared in Experimental Example 6 87.5 Application Example 7 Carbon-based catalyst prepared in Experimental Example 7 83.7 Application Example 8 Carbon-based catalyst prepared in Experimental Example 8 81.1 Application Example 9 Carbon-based catalyst prepared in Experimental Example 9 76.3 Application Example 10 Carbon-based catalyst prepared in Experimental Example 10 75.4 Application Example 11 Carbon-based catalyst prepared in Experimental Example 11 77.6 Comparative Example 4 Carbon-based catalyst prepared in Comparative Example 1 27.5 Comparative Example 5 Carbon-based catalyst prepared in Comparative Example 2 85.7 Comparative Example 6 Carbon-based catalyst prepared in Comparative Example 3 23.5
[0073] Table 3 Cyclic performance test results of hydrothermally stable catalysts
[0074]
Claims
1. A method for preparing a hydrothermally stable carbon-based catalyst, characterized in that: include: (1) adding lignin to an alkaline solution, then adding a metal salt, and centrifuging to obtain a lignin-metal complex; (2) Mixing the lignin-metal complex with a solvent gel reagent to obtain a mixture, stirring the mixture, centrifuging and separating to obtain a precipitate, and drying and calcining the precipitate to obtain a carbon-based catalyst.
2. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 1, characterized in that: In the mixture, the content of the solvent gel agent is 1wt%-80wt%.
3. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 2, characterized in that: In the mixture, the content of the solvent gel agent is 30wt%-50wt%.
4. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 1, characterized in that: The solvent gel reagent is one or more of polyvinyl alcohol, chitosan, carboxymethyl cellulose, starch, agar, and gelatin.
5. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 4, characterized in that: The solvent gel agent is polyvinyl alcohol.
6. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 1, characterized in that: The calcination temperature is 400° C.-800° C., and the heat preservation time is 30-180 minutes.
7. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 6, characterized in that: The calcination holding time is 60-120 minutes.
8. The method for preparing a hydrothermally stable carbon-based catalyst according to claim 1, characterized in that: The alkaline solution is one or more of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, and a lithium hydroxide solution; The metal salt is one or more of tin chloride, ferric chloride, magnesium chloride, cobalt chloride, aluminum chloride, magnesium nitrate, aluminum nitrate and ferric nitrate.
9. A hydrothermally stable carbon-based catalyst, characterized in that: The catalyst is prepared by the method for preparing a hydrothermally stable carbon-based catalyst according to any one of claims 1 to 8.
10. Use of the hydrothermally stable carbon-based catalyst according to claim 9 in the dehydration of biomass to prepare furfural, characterized in that: include: Xylose is used as a reaction substrate, and the reaction system is a reaction solvent of dichloromethane and water. Xylose and the hydrothermally stable carbon-based catalyst are added to a hydrothermal reactor, and then the reaction solvent is added. The reaction is carried out at 140° C. to 210° C. for 60 to 150 minutes, and the reaction is cooled and filtered. The filter residue is the carbon-based catalyst, which is washed and dried for standby use. The filtered liquid is used for quantitative analysis of furfural contained therein by high performance liquid chromatography.
Citation Information
Patent Citations
Preparation method of lignin-based bimetallic catalyst and application of lignin-based bimetallic catalyst in hydrogen evolution by electrolyzing water
CN114875443A
Lignin-based sulfonated carbon catalyst as well as preparation method and application thereof
CN117101719A